Non‐verbal communication in meetings of psychiatrists and patients with schizophrenia. (6th August 2014) - Lavelle, M.; Dimic, S.; Wildgrube, C.; McCabe, R.; Priebe, S.
<x xml:space="preserve">Abstract</x> Objective Recent evidence found that patients with schizophrenia display non‐verbal behaviour designed to avoid social engagement during the opening moments of their meetings with psychiatrists. This study aimed to replicate, and build on, this finding, assessing the non‐verbal behaviour of patients and psychiatrists during meetings, exploring changes over time and its association with patients' symptoms and the quality of the therapeutic relationship. Method 40‐videotaped routine out‐patient consultations, involving patients with schizophrenia, were analysed. Non‐verbal behaviour of patients and psychiatrists was assessed during three fixed, 2‐min intervals using a modified Ethological Coding System for Interviews. Symptoms, satisfaction with communication and the quality of the therapeutic relationship were also measured. Results Over time, patients' non‐verbal behaviour remained stable, whilst psychiatrists' flight behaviour decreased. Patients formed two groups based on their non‐verbal profiles, one group (n = 25) displaying pro‐social behaviour, inviting interaction and a second (n = 15) displaying flight behaviour, avoiding interaction. Psychiatrists interacting with pro‐social patients displayed more pro‐social behaviours (P < 0.001). Patients' pro‐social profile was associated reduced symptom severity (P < 0.05), greater satisfaction with communication (P < 0.001) and positive therapeutic relationships (P < 0.05). Conclusion Patients' non‐verbal behaviour during routine psychiatric consultations remains unchanged, and is linked to both their psychiatrist's non‐verbal behaviour and the quality of the therapeutic relationship.